The Majority of Boys Having Orchidopexy for Congenital Nonsyndromic Cryptorchidism during Minipuberty Exhibited Normal Reproductive Hormonal Profiles - Hildorf, Simone; Hildorf, Andrea E.; Clasen-Linde, Erik; Cortes, Dina; Walther-Larsen, Søren; Li, Ruili; Hutson, John M.; Thorup, Jorgen (European Journal of Pediatric Surgery, 2021)
Introduction The activation of the hypothalamic–pituitary–gonadal axis that occurs in male minipuberty during the first 5 months of life is important for early germ cell development. Orchidopexy during minipuberty may improve fertility potential as the germinative epithelium may benefit from the naturally occurring gonadotropin stimulation. We hypothesize that most boys with congenital nonsyndromic cryptorchidism display normal reproductive hormonal profiles and histological findings during minipuberty.Methods We included boys with congenital nonsyndromic cryptorchidism who underwent orchidopexy at less than 160 days of age, having no potential for spontaneous resolution clinically. At surgery, testicular biopsies and reproductive hormones were collected and compared with normal reference values. We measured the germ cells (G/T) and type A dark spermatogonia number per tubule.Results Thirty-five boys aged 37 to 159 (median age: 124) days at orchidopexy were included, five were bilateral. G/T was below the normal lower range in 26% (9/35) of the cases. In six of these cases, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were above 97.5 percentile, whereas one case had FSH below 2.5 percentile. Totally, 97% (33/34, one FSH was missing) exhibited a normal LH/FSH ratio. LH was more often above 97.5 percentile than FSH: 34% (12/35) versus 3% (1/34, p < 0.001). Inhibin B was below 2.5 percentile in 17% (6/35) of cases who all proved FSH above normal mean and four had LH above normal mean.Conclusion Generally, reproductive hormonal profiles of the cryptorchid boys exhibited normal minipubertal pattern. Thus, 26% of the boys had reduced germ cell number, and transient hypogonadotropic hypogonadism could be suspected in few cases.
Keywords: cryptorchidism; minipuberty; reproductive hormones; hypothalamic-pituitary-gonadal axis; germ cells